Using the HR intranet: an exploratory analysis of its impact on managerial satisfaction with the HR function - Alleyne, Cheryl; Kakabadse, Andrew P.; Kakabadse, Nada K. (Emerald, 2007)
The purpose of this paper is to explore the impact of the use of the human resources (HR) intranet at managerial levels in terms of internal customer satisfaction with the HR function.